How project-based collaborative learning affect on numeracy ability of elementary school teacher education students - Ni Luh Sakinah Nuraini; Puri Selfi Cholifah; Titis Angga Rini; Davina Aurelia; Silva Nabila (Psychology, Evaluation, and Technology in Educational Research, 2025)
Based on project-based collaborative learning, this study attempts to evaluate the numeracy skills of prospective elementary education teachers. The study design is pretest-posttest control group, and the research methodology is experimental and quantitative. Purposive sampling strategies are used to create experimental and control classes.While project assignments are completed individually in the control class, they are administered in groups to the experimental class. Ten multiple-choice and yes-or-no (objective) questions are used in the pre-test and post-test results to gather information on students' numeracy proficiency. Project-based collaborative learning research findings are applied to enhance the numeracy skills of prospective elementary education teachers. The score's outcomes after acquiring the experimental class were 0.001 and The experimental class used group projects, while the control class used individual projects. The control class's pre-test and post-test collaborative learning results differed by less than 0.001.